The Innovative Management in the Field of Inclusive Education and its Impact on the Public Health in the Republic of Kazakhstan - Adayeva, Nazykul; Satkaliyeva, Tamara (International Journal of Economics and Financial Issues, 2016)
In this article, the author studied the problem and the conditions of inclusive education, the legal and regulatory framework, scientific and methodological support of the organization include children with disabilities in the development of a common educational space through the introduction of innovative target project of inclusive education and a sociological survey. Based on the results of the research society's willingness to inclusive education are considered the main directions for the convergence of general and special education systems in matters aimed at obtaining a full education of this category of children. Management inclusive education involves the formation of a special body control and the model of inclusive education in the Republic of Kazakhstan. Keywords: Management; Implementation; Innovation; Development; Inclusive education; Public health, Policy. JEL Classifications: I2, O3